301 1000 Cases of Surgically Treated Aneurysmal Subarachnoid Haemorrhage: Changes in Practice and Clinical Outcomes. (1st April 2022) - Budohoski, Karol P.; Tajsic, Tamara; Bal, Jarnail; Levrini, Virginia; Guilfoyle, Mathew; Helmy, Adel; Kirkpatrick, Peter; Kirollos, Ramez; Trivedi, Rikin
Abstract : INTRODUCTION: Aneurysmal subarachnoid haemorrhage (aSAH) remains a complex and multidisciplinary pathology. With endovascular methods expanding fewer patients are treated surgically. METHODS: All patients following surgery for aSAH between 2007 - 2019 were included. Baseline characteristics outcomes were analysed. We compared outcomes between experienced (=50 independent cases) and non-experienced surgeons (<50 independent cases), and high-volume (=20 cases/year) and low-volume surgeons (<20 cases/year). RESULTS: 970 patients with 1003 aneurysms were identified with median age 56. 73.8% were WFNS grade 1 or 2. The majority of aneurysm were on the middle cerebral artery (41.4%), anterior communicating artery (27.6%) and posterior communicating artery (17.5%). 37.4% of aneurysm were <7 mm in size. Technical error rate was 6%, resulting in a post-operative infarct in 4.9% of patients. 19 patients (2%) died within 30 days of admission. There were no significant changes in technical error rates or post-operative infarcts or death (p = 0.79 and p = 0.77 respectively) over the study period. There was no difference in post-operative infarctions between experienced and non-experienced surgeons (p = 0.28), but there was a difference when comparing high-volume vs. low-volume surgeons (p = 028). CONCLUSION: We present real world data on surgical indications and outcomes after aSAH. We believe that this constitutes important data demonstrating good retention of skills and good clinical outcomes in a very dynamic field of cerebrovascular surgery. We also demonstrate a relationship between surgical case volume and outcomes.